2021
DOI: 10.1021/acscatal.1c02558
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Driven α-Allylation of Carboxylic Acids

Abstract: A boron-catalyzed α-allylation of carboxylic acids with allylsulfones under blue LED irradiation conditions is developed. We propose that photoexcitation of catalytically generated boron enediolates induces single-electron transfer to the allylsulfones. Subsequent C−C bond formation through a radical reaction constructs sterically demanding quaternary carbon centers at the position α to the carboxy group. The π-extended ligand on the boron atom is likely the key for efficient photoexcitation of the boron enedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Moreover, control experiments were carried out in alternating periods of irradiation and darkness. The experiments results showed that the reaction process was interrupted when removing the light source, while the reactivity was aroused again in the presence of light (Figure b), which further indicated that irradiation was an important component of the reaction . Only an yield of 8% was obtained by adding individual eosin Y–2Na as the photocatalyst in this catalytic experiment (Table , entry 4); this result is in agreement with that of the reported literature .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, control experiments were carried out in alternating periods of irradiation and darkness. The experiments results showed that the reaction process was interrupted when removing the light source, while the reactivity was aroused again in the presence of light (Figure b), which further indicated that irradiation was an important component of the reaction . Only an yield of 8% was obtained by adding individual eosin Y–2Na as the photocatalyst in this catalytic experiment (Table , entry 4); this result is in agreement with that of the reported literature .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Sawamura, Shimizu and co-workers described 132 the direct α-allylation of carboxylic acids employing allyl sulfones. The strategy is based on the formation of a boron-endiolate using a boron catalyst bearing a π-extended ligand to ensure visible light absorption.…”
Section: Catalytic C–c Bond Forming Reactionsmentioning
confidence: 99%
“…In their work, CÀC bond formation proceeded through single-electron transfer from photoexcited boron enediolates to the allylsulfones. [9] Scheme 1. Catalytic activations and transformations of carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%